Comparison of diferent diagnostic tests in dogs uninfected and naturally infected with visceral leishmaniasis - Sassaki, C. Y. [UNESP]; Colodel, M. M. [UNESP]; Ferreira, I. [UNESP]; Nogueira, F. S.; Lucheis, Simone Baldini [UNESP]; Langoni, Hélio [UNESP]; Rocha, Noeme Sousa [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2011)
Uninfected dogs (n = 10) and those naturally infected with leishmaniasis (n = 10) were subjected to several diagnostic tests, namely: hemoculture, polymerase chain reaction (PCR) of hemoculture, indirect immunofuorescence (RIFI), cytological examination of lymph node aspirate, culture of lymph node aspirate and PCR of lymph node aspirate. RIFI - followed by PCR of lymph node aspirate culture - presented more positive results in infected dogs than in uninfected ones. In infected animals, RIFI was more efective than PCR of lymph node aspirate culture. There was no statistical diference in positivity between RIFI and hemoculture; lymph node aspirate culture/cytological examination of lymph node aspirate and PCR of hemoculture; and between PCR of lymph node aspirate culture and PCR of hemoculture. All infected and uninfected animals had positive and negative results in at least one test. In conclusion, the association of several tests improves the efcacy of canine visceral leishmaniasis diagnosis.
Keywords: Diagnosis; Dogs; Visceral leishmaniasis; Animal experiment; Animal parasitosis; Aspiration cytology; Blood culture; Controlled study; Diagnostic test; Differential diagnosis; Dog; Immunofluorescence; Laboratory diagnosis; Leishmania; Lymph node biopsy; Nonhuman; Polymerase chain reaction; Visceral leishmaniasis; Animalia; Canis familiaris